Scoping Review: Paparan Debu Kayu terhadap Nilai Fungsi Paru dan Gejala Klinis pada Pekerja Industri Kayu - Rinal Pasya Nur Fauzan; Frasenda Sjafei; Lisa Adhia Garina (Bandung Conference Series: Medical Science, 2022)
Abstract. The wood industry is one type of industry that has a high risk of exposure to wood dust. Wood dust is one of the exposures in the workplace and a causative agent of respiratory problems. Respiratory problems being one of the health problems for wood industry workers. This study aims to examine exposure to wood dust on the value of lung function and clinical symptoms that occur in wood industry workers. Method that is used in this study is scoping review with the population is international articles. The databases used were Pubmed, ScienceDirect, Paripex-Indian Journal Of Research, International Journal Of Research In Medical Science and Springer Link. The number of journals obtained was 2,278, screening was carried out using inclusion criteria, PICOS and the final result 12 journals were obtained. The study design was using cross-sectional and cohort. The research intervention was exposure to wood dust. The measurement parameters in the selected journals varied including pulmonary function testing, FEV1 values, forced vital capacity (FVC), peak expiratory flow rate (PEFR), as well as clinical symptoms that arise in wood industry workers. The results of 12 journals that have been studied showed that there were clinical respiratory tract disorders in wood workers, 4 of them showed no significant effect on lung function, and 6 journals showed changes in lung function values ​​in wood industry workers. Abstrak. Industri kayu merupakan salah satu jenis industri yang memiliki risiko tinggi terhadap paparan debu kayu. Debu kayu menjadi salah satu pajanan di tempat kerja dan merupakan agen penyebab gangguan pernafasan. Gangguan pernafasan menjadi masalah kesehatan pada pekerja industri kayu. Penelitian ini bertujuan untuk mengkaji paparan debu kayu terhadap nilai fungsi paru dan gejala klinis yang timbul pada pada pekerja industri kayu. Penelitian ini menggunakan metode scoping review dengan populasi artikel internasional yang berkaitan. Database yang digunakan, yaitu Pubmed, ScienceDirect, Paripex-Indian Journal Of Research, International Journal Of Reasearch In Medical Science dan Springer Link Jumlah jurnal yang didapat 2.278 dan dilakukan penapisan dengan kriteria inklusi dan PICOS hingga didapatkan 12 jurnal. Desain penelitian menggunakan cross-sectional, dan cohort. Intervensi penelitian ini paparan debu kayu. Parameter pengukuran pada jurnal terpilih bervariasi diantaranya pengujian fungsi paru, nilai FEV1, kapasitas vital paksa (FVC), peak expiratory flow rate (PEFR), serta gejala klinis yang timbul pada pekerja industri kayu. Hasil 12 jurnal yang dikaji menunjukan adanya gangguan klinis saluran pernapasan pada pekerja kayu, 4 diantaranya menunjukan tidak adanya pengaruh fungsi paru yang signifikan, dan 6 jurnal menunjukkan adanya perubahan nilai fungsi paru pada pekerja industri kayu.